(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Availability of modern medicine increased in India. At the same time misuse of drugs is significantly increased worldwide which leads to resistance and increase the prevalence of ADR. To restrict the misuse of drugs India made National List of Essential Medicines (NLEM). Materials and Methods: The present study conducted in department of Pharmacology, Dhanalakshmi Srinivasan Medical College and Hospital, Siruvachur, Tamil Nadu. This study collected list of drugs from prescription in out patients. Data related name of the drug, dose, frequency, formulation, how many drugs prescribed per prescription and number of drugs per prescription was recorded and analysed. Statistical Package for Social Sciences (SPSS 20.0) version used for analysis. Results: A total of 682 drugs were prescribed last 6 months for outpatients. Maximum number of drugs prescribed in the month of April and least in March. 5 is the average of number of drugs per patient. 53% of drugs prescribed in generic name. Antibiotic use is high in the month of December least in the month of January. In December 61% patients received medication in the form of injection. December, February and April 60% drugs were prescribed form essential drug list. Conclusion: The study indicates the need to improve rational drug prescribing, increase generic prescribing practices, and enhance adherence to essential medicine guidelines in outpatient departments.